Coagulopathy in severe, isolated traumatic brain injury: A prevalence study - Lawrie, Ruchi (Department of Anaesthesia and Perioperative Medicine, 2019)
Introduction: Traumatic brain injury (TBI) is an important cause of morbidity and mortality in the developing world, and remains the leading cause of death and long-term disability in young adults. Hypocoagulopathy is a well described sequela of severe TBI and is associated with prolonged intensive care unit stays and poor outcomes. This study was conducted to determine the prevalence of coagulopathies in patients with severe, isolated TBI. The secondary outcome was to note any difference in the prevalence of detected coagulopathy between blunt and penetrating TBI. Methods: This is a prospective observational study of fifty patients with severe, isolated TBI (AIS head >3, AIS body <3), presenting to, or were referred to Groote Schuur Hospital. We drew blood for International Normalised Ratio (INR), activated partial thromboplastin time (aPTT), platelets count, sodium, potassium, urea and thromboelastography (TEG) on all patients at 12 hours (±3 hours), 36 hours (±3 hours) and eligible patients at 60 hours (±3 hours) post injury. Coagulopathy was defined as any one of the following: platelet count<120 x 109/L, INR>1.2, PTT>37 seconds, R time<4 minutes or >8 minutes, K time>4 minutes, α angle<47˚ or >74˚, maximum amplitude<54 mm or >72mm, EPL>15%, LY30>8 %, coagulation index<-3 or >3. Results: The patients were mostly male (n=47), with a mean age of 31 years. Median AIS head and body were 5 and 1, respectively. Thirty-six patients sustained blunt, and the remaining 14 penetrating trauma. Sixteen of the fifty patients demised during the course of the study. The cumulative prevalence of coagulopathy, as diagnosed by TEG, was 84% as diagnosed by TEG. Of the total 109 TEGs, 59 samples were hypercoagulable, 10 were hypocoagulable and the remaining 40 normal. There was poor correlation between laboratory-based coagulation assessments and TEG. Conclusions: Contrary to what is reported in the literature, we found little evidence of a hypocoagulable state as defined by TEG (10 of the 109 samples). Many patients were significantly hypercoagulable (59 of the 109 samples) according to criteria specified by the TEG manufacturer. When considering the CBT results, we had a much higher number of hypocoagulable samples (72 of the 109 samples), with none showing a hypercoagulable state. Moreover, there was poor correlation between coagulation status as measured by TEG described and that found on conventional blood testing. No significant differences in the prevalences of coagulopathy amongst blunt and penetrating mechanisms of injury were noted. Some differences in fluid balance and presenting vitals in the hypocoagulable group when compared to the normal and hypercoagulable groups were noticed, but this does not attain any statistical significance due to the small numbers of hypocoagulable patients in our study.